أهمية استراتيجية تحويل الموارد البشرية (trh) في تعزيز أنشطة البحث والتطوير وتحسين مؤشرات الأداء - بن سعادة ،مفيدة; دخاخني ،وهيبة; بوفلفل، سهام (جامعة الوادي University of Eloued, 2025)
The study aimed to explore the importance of the Human Resource Transformation Strategy (TRH) at Sonatrach during the period between 2019 and 2021 in developing research and development activities and improving performance indicators. The study relied on a descriptive and analytical approach to collect information about the study variables and their relationships, and a case study approach that focuses on analyzing various types of capital ratios, including working capital, total working capital, private working capital, and foreign working capital. Additionally, the approach involves analyzing key indicatorssuch as turnover and sales imports, and exports.The study concluded with several key findings, with the most significant being the contribution of Human Resources Transformation Strategy (TRH) in developing research and development activities and improving performance indicators at Sonatrach during the study period. The study also provided several recommendations, the most notable being the importance of adopting agile human resource management that helps in developing flexible financial plans that can adapt to the demands of contemporary crises.
The Importance of Human Resources Transformation Strategy (TRH) in Enhancing Research and Development Activities and Improving Performance Indicators - A Case Study of Sonatrach Company during the 2019-2021 Period.
Keywords: الموارد البشرية; تحويل الموارد البشرية; أنشطة البحث والتطوير; مؤشرات الأداء; Human Resource; Human Resource Transformation (TRH); Research and Development Activities; Performance Indicators; Sonatrach.